Challenges of Virtual Design and Construction Implementation in Public Projects - Prado Lujan, Guillermo (2021)
The Peruvian AEC industry has started implementing VDC and BIM in public projects due to recent regulations that state the progressive adoption of BIM (as a methodology) in public construction. Regardless of the benefits of these new approaches, some challenges to VDC implementation have emerged as a response to the resistance to change of the Peruvian AEC industry, which is stronger in the Peruvian public sector. The aim of this paper is to present the challenges found in the author´s VDC implementation experience in a public project, as part of the third VDC Certificate Program in Lima lead by CIFE from Stanford University. These challenges will be identified based on a schema, constructed by the literature review. The results show that the main challenges found are the lack of commitment and the lack of collaboration between stakeholders. These results suggest the need to overcome this resistant-to-change environment by focusing on training programs and conducting capability assessments within public institutions before start implementing VDC, so more benefits will be achieved by the Peruvian public institutions.